Determination of correlated uncertainties of sestamibi- 99mTc marking. (July 2016) - Sousa, C H S; Gama, A; Camilo, T G N; Mesquita, C T; Peixoto, J G P
Abstract: The input quantities determination involved in radiopharmaceutical marking used in heart scans allowed to estimate the combined and associated standard uncertainty with the process. The U value demonstrated that any parameter of the quality control process can be compared and correlated to obtain a real value and validation method, indicating or not, the adequacy of institutional practices and reinforcing the importance of the uncertainties associated to the results in medicine.